2005
DOI: 10.1677/jme.1.01746
|View full text |Cite
|
Sign up to set email alerts
|

Signaling cross-talk between IGF-binding protein-3 and transforming growth factor-β in mesenchymal chondroprogenitor cell growth

Abstract: Cartilage formation is driven by mesenchymal chondroprogenitor cells (MCCs) that proliferate and differentiate into chondrocytes. The molecular mechanisms by which growth factors regulate MCC fate are not well defined. Insulin-like growth factor binding protein-3 (IGFBP-3) has intrinsic bioactivity that is independent of IGF binding. We previously reported that IGFBP-3 has IGF-independent antiproliferative and apoptotic effects in MCCs, and requires STAT-1 activation to mediate its apoptotic effect. Transformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 72 publications
2
9
0
Order By: Relevance
“…We found that CTRP1 induces activation of ERK1/2 in immature proliferating chondrocytes, whereas it had no effect on the activities of JNK1/2, p38 MAPK and Akt, and none of their phosphorylated forms was detected (data not shown). Indeed, the ERK1/2 pathway is known to be involved in controlling proliferation of immature proliferating chondrocytes (O'Rear et al, 2005;Akiyama et al, 2006). We next investigated the effects of the MEK1/2 inhibitor U0126 on the proliferation of CTRP1-stimulated immature proliferating chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We found that CTRP1 induces activation of ERK1/2 in immature proliferating chondrocytes, whereas it had no effect on the activities of JNK1/2, p38 MAPK and Akt, and none of their phosphorylated forms was detected (data not shown). Indeed, the ERK1/2 pathway is known to be involved in controlling proliferation of immature proliferating chondrocytes (O'Rear et al, 2005;Akiyama et al, 2006). We next investigated the effects of the MEK1/2 inhibitor U0126 on the proliferation of CTRP1-stimulated immature proliferating chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, enhanced proteolysis of IGFBP-3 by ADAM12 would increase the bioavailability of IGF-1, thereby also supporting MPC proliferation and chondrogenic differentiation. On the other hand, it has also been shown that the apoptosis-potentiating and anti-proliferative activity of IGFBP-3 on MSCs may be antagonised through a TGF-β-dependent ERK pathway [52], suggesting that the proliferative, chondrogenic and anti-apoptotic effects of PPS on MPCs could be mediated by their increased production of TGF-β.…”
Section: Discussionmentioning
confidence: 99%
“…They identified the signal transducer and activator of transcription (STAT)1 to be an intracellular signaling and transcriptional target of the apoptotic effect of IGFBP-3 in chondrogenesis (45). Recently, O'Rear et al (33) have shown that there is cross talk between the IGFBP-3-dependent STAT1 signaling and the TGF-␤-dependent ERK pathway that regulate mesenchymal chondroprogenitor cell proliferation and differentiation. In adipocytes, TNF-␣ is well known to inhibit differentiation (35,52).…”
Section: Discussionmentioning
confidence: 99%